PEDAGOGIC FUNCTIONS OF TEACHERS’ CODE-SWITCHING IN GARUDA BILINGUAL KINDERGARTEN - I Gusti Ayu Arya Satyani Pinatih (Lingua Scientia, 2019)
Even though codeswitching has become a natural phenomenon and occurred in regular basis during the teaching  and  learning  process  in  bilingual  classroom,  the  pedagogic  analysis  of  the  occurring  switches should  be  taken  into  account  to  figure  out  whether  the  switches  are  indeed  a  pedagogic  tool  used  by bilingual  teachers  for  the  comprehension  and  achievement  of  the  lesson  content.  Therefore,  the objective  of  this  study  is  to  figure  out  the  functions  of  teachers’  code‐switching  during  classroom teaching  and  learning  process  in  Garuda  Bilingual  Kindergarten.  This  study  was  conducted  using  a descriptive  qualitative  design.  The  data  were  collected  through  classroom  observation  and  recordings. The  obtained  data  were  analyzed  based  on  the  coding  categories  of  pedagogic  function  theory.  The findings  indicate  that  the  functions  of  the  occurring  code‐switching  are:  1)  instructional  for  content acquisition,  2)  reformulation  of content,  3)  facilitation,  and  4)  habitual.  The  result  of  this  study  is expected  to  be  useful  especially  for  teachers  to  know  the  role  of  code‐switching  in  supporting  the emergent  bilinguals  during  classroom  teaching  and learning  process  as  well  as  to  help  teachers  plan  a more effective language strategy.